Riparian willow dynamics and their interaction with environmental and biological factors in the elk winter range of Rocky Mountain National Park (Colorado) - a multi-scale analysis - Peinetti, Hector Raul, author; Coughenour, Michael B., advisor; Swift, David M., committee member; Detling, James K., committee member; Kalkhan, Mohammed, committee member (Colorado State University. Libraries, 2000)
Changes in willow populations and their association with different causative factors were evaluated in two valleys of the elk winter range of Rocky Mountain National Park (Colorado). Studies at the individual, population, and landscape scale were conducted, and results from these studies were incorporated into a spatial, process based model (SAVANNA). Morphological and physiological characteristic of willows protected and unprotected from elk browsing were compared. Browsing induced plant canopy changes and reduced the relative amount of carbon allocated belowground, but aboveground productivity was not changed. By suppressing height growth, elk browsing induced short willow morphotypes (< 1.5 m), which contrasted with tall willow plants (> 2 m) that grew in the same valley. Short willows that grew under protection from elk increased plant height compared to unprotected willows, but 5 years of protection was not long enough for these willows to acquire the height frequency distribution of a tall willow population. Landscape change analysis of willow cover was conducted by photo-interpretation of historic (1937/1946) and recent (1996) aerial photos. A decrease of willow cover of approximately 20% and more than 50% reduction in river length and water surface area were determined in this period. Deeper water tables that were produced by a decline of beavers and by human made ditches seem to explain most of the willow decline. The model estimated that the transition from short to tall willow population could occur in approximately 10 years, under no elk herbivory. This transition was inhibited at elk densities higher than 50 elk/km2. Interaction between water table depth and elk density was predicted in the model. The beaver decline appeared to play the most significant role in the decline in willow. The increases in elk density that have occurred since the mid-1960's could have contributed to this decrease, but the major effect of elk was apparently an increase in the proportion of short willow morphotypes.
Keywords: ecology; botany; forestry